CCL2 Inhibitor Bindarit Improve Postoperative Cognitive Function by Attenuating Pericyte Loss-Related Blood–Brain Barrier Disruption and Neuroinflammation - Hui Yuan; Bo Lu; Daofan Sun; Junping Chen; Xiangming Fang (Mediators of Inflammation)
Perioperative neurocognitive disorder (PND) is a common complication in elderly patients undergoing surgery and anesthesia and associated with the impaired recovery. Previous studies have demonstrated that PND was correlated with the pericyte (PC) loss in brain, but the underlying mechanisms remain unclear. This study investigates whether C–C motif chemokine ligand 2 (CCL2) in hippocampal tissues contributes to postoperative PC injury, blood–brain barrier (BBB) disruption, neuroinflammation, and cognitive dysfunction. Sixteen-month-old C57BL/6 mice underwent tibial fracture surgery to induce PND. CCL2 expression in hippocampal tissues was downregulated using intraperitoneal injections of 200 mg/kg daily Bindarit for 4 days prior to surgery. Behavioral tests were conducted on the third day postsurgery and brain tissues were collected. Western blotting assessed CCL2 expression in the hippocampus, immunofluorescence evaluated PC coverage, BBB integrity, and neuroinflammation, and transmission electron microscopy (TEM) examined BBB microstructure. Bindarit effectively inhibited the surgery-induced increase in hippocampal CCL2 expression and improved postoperative cognitive function. Behavioral tests, including the open field (OF) test and novel object recognition (NOR) test, indicated enhanced locomotor activity and short-term memory in Bindarit-treated mice compared to controls. Immunofluorescence analysis revealed that Bindarit treatment mitigated the reduction in capillary length and tight junction (TJ) protein expression, specifically claudin-5 and occludin, which was seen with decreased PC coverage. Additionally, Bindarit suppressed the activation of hippocampal microglia and astrocytes, as evidenced by reduced Iba-1 and GFAP staining. TEM analysis confirmed that Bindarit preserved BBB microstructure integrity postsurgery. This study demonstrates that the CCL2 inhibitor Bindarit significantly reduces the incidence of PND by preventing PC loss, thereby protecting the BBB and alleviating neuroinflammation. These findings suggest that targeting CCL2 could be a potential therapeutic strategy for preventing and treating PND.